1978
DOI: 10.1099/00221287-104-2-325
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Susceptibility of Candida albicans to the Polyenoic Antibiotics Nystatin and Amphotericin B

Abstract: Factors influencing the interaction between Candida albicans and the polyenoic antibiotics nystatin and amphotericin B have been investigated using a K+-specific electrode to measure polyene-mediated efflux of cellular K+. In batch cultures, sensitivity was a function of culture age. Using continuous (chemostat) cultures, the influence of growth-limiting substrate, specific growth rate, growth temperature and growth pH were examined. Carbonlimited cultures showed the highest sensitivity of those substrates tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0

Year Published

1979
1979
2001
2001

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…Most studies have shown minor or no differences in MICs of various antifungal agents tested against yeasts at temperatures ranging from 22 to 37°C (1,3,13,16,17). However, Block et al (2) noted a considerable increase in the susceptibility of Cryptococcus neoformans to flucytosine at 37°C compared with that at 32°C, while precisely the opposite effect of temperature was noted by Johnson et al, working with nystatin (14), and Galgiani et al, working with flucytosine (11), both in tests with Candida spp. An incubation temperature of 35°C has emerged in some recent reports as preferable both to 37°C (5) and to 30°C (23,25) for optimal reader agreement with visual MIC endpoints.…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…Most studies have shown minor or no differences in MICs of various antifungal agents tested against yeasts at temperatures ranging from 22 to 37°C (1,3,13,16,17). However, Block et al (2) noted a considerable increase in the susceptibility of Cryptococcus neoformans to flucytosine at 37°C compared with that at 32°C, while precisely the opposite effect of temperature was noted by Johnson et al, working with nystatin (14), and Galgiani et al, working with flucytosine (11), both in tests with Candida spp. An incubation temperature of 35°C has emerged in some recent reports as preferable both to 37°C (5) and to 30°C (23,25) for optimal reader agreement with visual MIC endpoints.…”
mentioning
confidence: 80%
“…In all of the reports cited, MIC was the susceptibility endpoint used to determine the effect of temperature, with one exception in which ion efflux in response to nystatin was measured with a K+ electrode (14). However, it has often been stressed that azole-derivative antifungal agents frequently cause partial inhibition of yeast growth at concentrations well below the MIC (1,8,12,19,21).…”
mentioning
confidence: 99%
“…By contrast the use of chemically complex undefined media such as SAB medium is not recommended (19,28) since undefined components that they may contain might interact with antifungal drugs (13,14,19,26). Furthermore, acidic media such as YNB and SAB, if they were used unbuffered, may inactivate amphotericin B, which is not stable at low pH (16,21).…”
Section: Discussionmentioning
confidence: 99%
“…These included 32 strains from a panel selected for their variable susceptibilities to an unrelated antifungal agent, flucytosine (18,21), and 7 strains selected from among clinical isolates from our collection. Another strain was isolated from a patient whose ketoconazole treatment failed (strain K3, also identified by others as KB [9,10,18]). A final C. albicans isolate, strain F662, used previously with strain C17 to evaluate the effect of inoculum size on results obtained with fluconazole (18), was also used for inoculum studies.…”
mentioning
confidence: 99%